2011
DOI: 10.1111/j.1528-1167.2010.02961.x
|View full text |Cite
|
Sign up to set email alerts
|

Management and long-term outcome in patients presenting with ictal asystole or bradycardia

Abstract: Summary Purpose:  Ictal asystole (IA) and ictal bradycardia (IB) are rare autonomic symptoms during epileptic seizures and may be potentially life‐threatening. Guidelines for the care of these patients are missing. The aim of this multicenter study was to evaluate the management and long‐term outcome in patients with IA and IB. Patients and Methods:  All patients with IA and IB were included from four epilepsy centers (Bielefeld, Kork, Marburg, and Zürich) from 2002 until 2009. Using a standardized assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
103
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(110 citation statements)
references
References 46 publications
6
103
0
1
Order By: Relevance
“…Four large retrospective studies in EEG/ECG-monitored epilepsy patients have similarly found the prevalence of ictal asystole to be 0.25%–0.40% in over 11,000 epilepsy patients, although these retrospective analyses likely underestimate the true prevalence. 5–8 Longer term monitoring may lead to increased detection of ictal asystole. In a study of 19 patients with refractory partial seizures who underwent ILR implantation, 7 had ictal bradyarrhythmia.…”
Section: Discussionmentioning
confidence: 99%
“…Four large retrospective studies in EEG/ECG-monitored epilepsy patients have similarly found the prevalence of ictal asystole to be 0.25%–0.40% in over 11,000 epilepsy patients, although these retrospective analyses likely underestimate the true prevalence. 5–8 Longer term monitoring may lead to increased detection of ictal asystole. In a study of 19 patients with refractory partial seizures who underwent ILR implantation, 7 had ictal bradyarrhythmia.…”
Section: Discussionmentioning
confidence: 99%
“…11 If this fails and there is documented recurrence of asystolic episodes, cardiac pacemaker implantation should be considered. Observational studies suggest that pacemakers can reduce falls and injuries due to seizure-induced syncope.…”
Section: Discussionmentioning
confidence: 99%
“…5 6 The mean prevalence of ictal asystole in all people with refractory focal epilepsy admitted for a vEEG recording was 0.318% (95% CI 0.316% to 0.320%). [7][8][9][10][11] Ictal asystole was only reported in people with focal epilepsy (table 1). Most of the ictal asystoles occurred during the course of a focal dyscognitive seizure (formally known as a complex partial seizure), on average starting 30 s after seizure onset.…”
Section: Ictal Asystolementioning
confidence: 99%
“…2,3 However, ictal bradycardia (IB) and IA are rare occurrences, with IA reportedly occurring in 0.27%-0.4% of monitored epilepsy patients. 4 Seizures in patients with IB and IA have been primarily associated with temporal lobe onset. 5 However, lateralization of such events has not been consistent.…”
Section: Oy-stersmentioning
confidence: 99%